Depression and anxiety in adolescents with cystic fibrosis in Brazil: prevalence, stability over time, and relationship with treatment adherence - Tatiana Rozov; Marcos Tadeu Nolasco da Silva; Maria Ângela Gonçalves Oliveira Ribeiro; Neiva Damaceno; Maria Angelica Pinheiro Santos Santana; Paulo Jose Cauduro Marostica; Roberta de Cássia Nunes Cruz Melotti; Valeria de Carvalho Martins; Carlos Antônio Riedi; Edna Lucia Santos de Souza; Norberto Ludwig Neto; Rodrigo Abensur Athanazio; et al. (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: Depression and anxiety have been documented in people with cystic fibrosis (CF), jeopardizing treatment adherence. To date, no studies have assessed the prevalence of psychosocial issues in adolescents with CF in Brazil. We sought to assess the prevalence of depression and anxiety in adolescents with CF in Brazil, as well as the impact of depression and anxiety on treatment adherence. Methods: This was a multicenter, prospective, observational, longitudinal study conducted between 2017 and 2019 at 14 CF referral centers in Brazil. We used standardized tools such as the nine-item Patient Health Questionnaire (for depression), the seven-item Generalized Anxiety Disorder scale (for anxiety), and the eight-item Morisky Medication Adherence Scale (for treatment adherence) in order to collect data on 218 CF patients at two different time points. Results: The prevalence of depression was 19.1% at time point 1 and 15.4% at time point 2. The prevalence of anxiety was 19.1% at time point 1 and 18.0% at time point 2. Depression and anxiety were significantly higher in female patients and lower in those who underwent home physiotherapy or had psychological support. Significant correlations were found between depression and anxiety at both time points, the associations being strongest at time point 1 (r = 0.68; p < 0.001). Most (66.7%) of the study participants reported low adherence to treatment, and the remainder reported either average adherence (in 28%) or high adherence (in 5.3%). Depression and anxiety showed inverse correlations with treatment adherence. Conclusions: The prevalence of depression and anxiety in adolescents with CF in Brazil appears to be similar to that reported in other countries, being higher in females and lower in those undergoing home physiotherapy or receiving psychological care. Depression and anxiety appear to correlate with lower treatment adherence. Treating psychosocial issues may effectively improve rates of treatment adherence in adolescents with CF.